A Generation Mechanism of Banded Plasmaspheric Hiss - Junhu Dong; Binbin Ni; Zheng Xiang; Zhiyong Wu (Geophysical Research Letters)
Abstract As a unique structure of plasmaspheric hiss emissions, banded hiss waves generally consist of an upper band above ∼200 Hz, a lower band below ∼100 Hz and a power gap in between. However, the generation mechanism of banded hiss remains unclear. Here we present a representative event of banded hiss co‐existing in both the plasmaspheric plume structure and the plasmasphere. The wave Poynting flux measurements and linear instability analysis suggest that banded hiss can be generated in the equatorial plume region. The ray tracing simulations further show that the plume structure enables banded hiss to propagate along the plasma density crest to higher latitudes, followed by the penetration into the plasmasphere. Our data analysis and modeling efforts provide a plausible mechanism for the generation of banded hiss, and also highlight the significant role of plume structure in the generation and propagation of magnetospheric whistler‐mode waves.